From Bakke to Hopwood: Does Race Affect College Attendance and Completion? - Light, Audrey; Strayer, Wayne (The Review of Economics and Statistics, 2002)
In light of recent, state-level actions banning racial preference in college admissions decisions, we investigate how whites and minorities differ in their college-going behavior. Using data from the National Longitudinal Survey of Youth, we estimate a sequential model of college attendance and graduation decisions that allows correlations among the errors. Our estimates reveal that minorities are more likely than observationally equivalent whites to attend colleges of all quality levels. Being a minority has a positive effect on graduation probabilities, but, overall, minorities are less likely than their white counterparts to complete college because they possess fewer favorable unobserved factors.